Increasing Repurchase Intention on Garuda Indonesia Airlines at Soekarno-Hatta International Airport - Made Dian Adi Wisnawan; Avira Mulia Revany; Erwin R. Manurung; Sinai Handayani (Green Publisher, 2025)
This study aims to examine the effect of service quality and price perceptions on repurchase intention through customer satisfaction on Garuda Indonesia airlines at Soekarno Hatta International Airport due to a decrease in the number of passengers from 2019 to 2021 and only increased in 2022 but not yet significant. The sample of this study were 160 respondents who used Garuda Indonesia airline. Data analysis using Structural Equation Modeling-Partial Least Square (SEM-PLS 4.0). The results of this study indicate that service quality has a positive and significant effect on repurchase intention. Price perception has a positive and significant effect on repurchase intention. Customer satisfaction has a positive and significant effect on repurchase intention. Service quality has a positive and significant effect on customer satisfaction. Price perception has a positive and significant effect on customer satisfaction. The results of this study can serve as a basis for Garuda Indonesia to increase repurchase intention by considering service quality and price perceptions that are aligned with the benefits.